A Numerical Study on the Effects of Ship-Generated Waves on a Moored Ship in Restricted Waterways Considering Initial Acceleration Process - Ziqiang Zheng; Lu Zou; Zaojian Zou (Journal of Marine Science and Engineering, 2023)
In order to develop a reliable numerical method to investigate the effects of ship-generated waves on a moored ship in restricted waterways, this paper takes the MASHCON2022 benchmark model test case as the study object and simulates the whole process of a ship passing a moored ship by using the unsteady Reynolds-Averaged Navier-Stokes (URANS) method coupled with the dynamic overset mesh technique. The initial acceleration process of the passing ship before approaching the moored ship is considered in the numerical simulations to reproduce the benchmark model tests more realistically. The numerical simulations with four acceleration modes are conducted. The comparisons among the numerical results and the test data verify that the prediction accuracy considering the acceleration process is obviously higher than that without the acceleration process, especially for the solitary wave system, and the results based on the linear acceleration agree with the test data best. The flow field results indicate that the impacts of the solitary wave system and the primary wave system on the moored ship are different: the solitary wave system induces significant positive pressures on the hull, while the primary wave system leads to remarkable negative pressures; both result in pronounced attitude variations of the moored ship, but the hydrodynamic forces and moments affected by the primary wave system are more pronounced.